Un marco metodólogico para la investigación pragmalingüística del texto dramático: análisis de diatriba de amor contra un hombre sentado de Gabriel García Márquez (2012)
ABSTRACT: This article presents some aspects of a pragmalinguistic analysis of Diatriba de amor contra un hombre sentado by Gabriel Garcia Marquez. First, it develops the theoretical considerations and methodological issues related to treatment of the dramatic text as a valid corpus for this type of research. Then it presents a pragmalinguistic analysis of the didascalia, from the review of the classification proposed by Hermenegildo (1986). The implications of such research are briefly discussed.